2000
DOI: 10.1046/j.1440-1630.2000.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Australian children on the Miller assessment for preschoolers compared with USA norms

Abstract: The aim of this study was to compare the performance of Australian children on the Miller assessment for preschoolers (MAP), to that of USA norms. The MAP (with Australian language changes) was administered to a sample of 218 Australian children across the six age groups of the test. Chi‐squared analysis, comparing scores of the Australian sample with the USA norms, detected significant differences between the two groups on all variables except the Verbal Index. Australian children obtained higher scores for F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
3
1
Order By: Relevance
“…Our finding for balance subset scale score was comparative with the study outcome done by Cushing et al (2008) on control group on static and balance function in children. The difference in findings in our study compared to the published age-adjusted mean could be due to the contribution of different culture and environment of the subject's life style, which may affect the skill and ability of the motor activities (Chow et al 2001;Hickey et al 2000 andSchneider et al 1995). This current study showed scale score for subset running, speed, and agility were negatively correlated with age.…”
Section: Bot-2contrasting
confidence: 82%
“…Our finding for balance subset scale score was comparative with the study outcome done by Cushing et al (2008) on control group on static and balance function in children. The difference in findings in our study compared to the published age-adjusted mean could be due to the contribution of different culture and environment of the subject's life style, which may affect the skill and ability of the motor activities (Chow et al 2001;Hickey et al 2000 andSchneider et al 1995). This current study showed scale score for subset running, speed, and agility were negatively correlated with age.…”
Section: Bot-2contrasting
confidence: 82%
“…Higher mean scores in Australian children tested using US norms have been reported on a number of developmental and intelligence tests, and it has been suggested that cultural issues may alter the rate of maturation as well as the performance on individual test items 24 25. The test's publishers suggest that the elevated scores are possibly due to demographic changes 26.…”
Section: Discussionmentioning
confidence: 99%
“…As the Vineland SEEC Scales were developed in the USA, it was important that the interview questions were culturally appropriate to the Australian parents and guardians in this research. In a study using the Miller assessment for preschoolers, which compared the performance of Australian children to that of the USA norms, Hickey, Froude, Williams, Hart and Summers (2000) changed particular test items to increase the test's cultural relevance to Australian children. The wording of three questions within the Vineland SEEC Scales was changed to suit the Australian sample in this study in order to increase the scales cultural relevance to Australia.…”
Section: The Vineland Social-emotional Early Childhood Scalesmentioning
confidence: 99%